2019
DOI: 10.1063/1.5089750
|View full text |Cite
|
Sign up to set email alerts
|

A directional fibre optic ultrasound transmitter based on a reduced graphene oxide and polydimethylsiloxane composite

Abstract: Strongly directional ultrasound sources are desirable for many minimally invasive applications, as they enable high-quality imaging in the presence of positioning uncertainty. All-optical ultrasound is an emerging paradigm that exhibits high frequencies, large bandwidths, and a strong miniaturisation potential. Here, we report the design, modelling, and fabrication of a highly directional fibre-optic ultrasound transmitter that uses a composite of reduced graphene oxide and polydimethylsiloxane as the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
0
36
1
Order By: Relevance
“…[8,13,14,16,20] To compare the generation efficiency with previous results, the 2D pressure field measurements were numerically backpropagated to the coating surface to yield a transduction efficiency of 0.024 MPa mJ −1 cm −2 . While this efficiency was lower than those recently presented for carbon nanotube-based coatings [8,16] (0.13-0.65 MPa mJ −1 cm −2 ) and graphene-based coatings [69] (0.21 MPa mJ −1 cm −2 ), the high damage threshold of the CIS-PDMS coating allowed for comparable absolute pressures to be achieved. The generated pressure increased linearly with laser fluence, as expected from PA excitation.…”
Section: Discussioncontrasting
confidence: 62%
“…[8,13,14,16,20] To compare the generation efficiency with previous results, the 2D pressure field measurements were numerically backpropagated to the coating surface to yield a transduction efficiency of 0.024 MPa mJ −1 cm −2 . While this efficiency was lower than those recently presented for carbon nanotube-based coatings [8,16] (0.13-0.65 MPa mJ −1 cm −2 ) and graphene-based coatings [69] (0.21 MPa mJ −1 cm −2 ), the high damage threshold of the CIS-PDMS coating allowed for comparable absolute pressures to be achieved. The generated pressure increased linearly with laser fluence, as expected from PA excitation.…”
Section: Discussioncontrasting
confidence: 62%
“…Recently, an all-optical alternative to electronic ultrasound transducers has been presented that uses light to both transmit and receive ultrasound. Using fibre optic technology, optical ultrasound sources [3][4][5][6][7][8] and detectors [9][10][11][12][13][14] are readily miniaturised, exhibit high bandwidths and sensitivities, and are immune to electromagnetic interference. Recently, a benchtop system has been demonstrated that used a single fibre optic ultrasound detector and a centimetre-scale monolithic photoacoustic ultrasound generator membrane to achieve video-rate two-dimensional imaging [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the OpUS probe can be optimised to provide improved lateral resolution. The divergence of the generated ultrasound beam could be reduced by using a concave ultrasound generating surface 13 or larger diameter planar surfaces, 14 to achieve a focus within tissue.…”
Section: Resultsmentioning
confidence: 99%